A case of neurosarcoidosis that presented with symptoms of Guillain–Barré syndrome. (4th April 2011) - Oldroyd, A; Dawson, T; Nixon, J
Abstract : This case report is of a patient who presented with clinical features suggestive of Guillain–Barré syndrome, who on investigation was found to have neurosarcoidosis. The patient was treated with high-dose corticosteroids and physiotherapy and he improved in condition substantially over 1 month. Neurosarcoidosis and its various presentations are discussed in the literature review.